Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/pen.24391
|View full text |Cite
|
Sign up to set email alerts
|

A new microcellular foam injection‐molding technology using non‐supercritical fluid physical blowing agents

Abstract: A new foam injection-molding technology was developed to produce microcellular foams without using supercritical fluid (SCF) pump units. In this technology, physical blowing agents (PBA), such as nitrogen (N 2 ) and carbon dioxide (CO 2 ), do not need to be brought to their SCF state. PBAs are delivered directly from their gas cylinders into the molten polymer through an injector valve, which can be controlled by a specially designed screw configuration and operation sequence. The excess PBA is discharged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Research has been conducted on modifications to the standard SCF process developed by MuCell V R . In particular, Yusa et al 47 have successfully shown that machine energy costs and material usage can be reduced by using N 2 and CO 2 at lower pressures than the super critical (SC) state. This was achieved by designing and implementing a similar system to the MuCell V R setup.…”
Section: Super Critical Fluidsmentioning
confidence: 99%
“…Research has been conducted on modifications to the standard SCF process developed by MuCell V R . In particular, Yusa et al 47 have successfully shown that machine energy costs and material usage can be reduced by using N 2 and CO 2 at lower pressures than the super critical (SC) state. This was achieved by designing and implementing a similar system to the MuCell V R setup.…”
Section: Super Critical Fluidsmentioning
confidence: 99%
“…In commercial applications, there are three types of injection foaming units that are widely used: (i) MuCell ® by Trexel Inc.; (ii) Optifoam developed by Institute of Plastic Processing (IKV) Sulzer Chemtech; and (iii) Ergocell developed in 2001 by Demag [102]. All studies used super-critical fluids (SCF).…”
Section: Methods and Parameters Associated With Cellulose Nanostrumentioning
confidence: 99%
“…These problems limit the production and application of foam injection molding to a certain extent. In the field of foam injection molding, many scholars have carried out a lot of research work on conventional physical foam injection molding [3][4][5][6], core-back physical foam injection molding [7][8][9][10] and gas counter pressure (GCP) foam injection molding [9][10][11][12][13]. Core-back foam injection molding [14][15][16][17][18][19][20][21][22][23][24][25] is to inject gas/polymer homogeneous system into the mold cavity first, and use high holding pressure to eliminate the cells generated in the filling process, then open the mold or withdraw the mold core at a certain distance to make the melt foam.…”
Section: Introductionmentioning
confidence: 99%